2023
DOI: 10.3390/insects14080693
|View full text |Cite
|
Sign up to set email alerts
|

Green Manure Crops as Food Source: Impact on the Performance of the Migratory Beet Webworm, Loxostege sticticalis (Lepidoptera: Pyralidae)

Abstract: The application of green manure is crucial for achieving sustainable agriculture and animal husbandry, but pest management is often overlooked. Conducting a risk assessment for insect pests in green manure is essential. The beet webworm, Loxostege sticticalis, a polyphagous insect, is currently experiencing an outbreak in northern China, and represents a significant migratory pest. A two-sex life table and flight mill test approach was used to comprehensively evaluate the effects of three major legume green ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
0
0
Order By: Relevance
“… 48 However, only a few studies support this perspective. While previous studies have already demonstrated the direct effects of GM crops on the growth potential of herbivorous insects, 37 , 49 , 50 our study focused on examining the effects of applying GM on the development, survival, and fecundity of herbivorous insects feeding on subsequent crops. In the present study, GM application had a significant effect on the performance of FAWs fed on subsequent maize crops.…”
Section: Discussionmentioning
confidence: 99%
“… 48 However, only a few studies support this perspective. While previous studies have already demonstrated the direct effects of GM crops on the growth potential of herbivorous insects, 37 , 49 , 50 our study focused on examining the effects of applying GM on the development, survival, and fecundity of herbivorous insects feeding on subsequent crops. In the present study, GM application had a significant effect on the performance of FAWs fed on subsequent maize crops.…”
Section: Discussionmentioning
confidence: 99%